Unveiling the dynamics of entrepreneurship among disadvantaged communities in developing economies: a cognitive perspective - Amar Johri; Mohammed Wamique Hisam; Mohammad Asif; Mohammad Shahfaraz Khan; Md. Faisal-E-Alam; Mohd Yasir Arafat; Zuhaib Ahmad; Asma Zaheer (Cogent Business & Management, 2024)
Entrepreneurship helps to mainstream the disadvantaged. In order to design policy for the promotion of entrepreneurship among disadvantaged people a proper understanding of entrepreneurship is imperative and cognition has been considered as the best interpreter of entrepreneurship. This study aimed to explore the driving forces and hindrances that influence disadvantaged individuals in their decision to initiate entrepreneurial endeavors. We are using a sample of 1173 people taken from the low-income population of India. The data is analyzed through the use of the Logistic regression technique. The result reflects that attitude, subjective norms, self-efficacy, perceived opportunities and role models encourage Indian disadvantaged to start business. This research contributes to two existing theories: challenge-based entrepreneurship and the theory of planned behavior. It also sheds light on a previously understudied group - disadvantaged entrepreneurs in developing economies. This knowledge can be used by policymakers to create programs that encourage entrepreneurship at the grassroots level.
Keywords: 650; Marginalized; india; disadvantaged entrepreneurs; cognition; developing economies